Electrophysiological characterization of male goldfish (Carassius auratus) ventral preoptic area neurons receiving olfactory inputs - Lado, Wudu E.; Spanswick, David C.; Lewis, John E.; Trudeau, Vance L. (Frontiers in Neuroscience, 2014)
Chemical communication via sex pheromones is critical for successful reproduction but the underlying neural mechanisms are not well-understood. The goldfish is a tractable model because sex pheromones have been well-characterized in this species. We used male goldfish forebrain explants in vitro and performed whole-cell current clamp recordings from single neurons in the ventral preoptic area (vPOA) to characterize their membrane properties and synaptic inputs from the olfactory bulbs (OB). Principle component and cluster analyses based on intrinsic membrane properties of vPOA neurons (N = 107) revealed five (I-V) distinct cell groups. These cells displayed differences in their input resistance (Rinput: I < II < IV < III = V), time constant (TC: I = II < IV < III = V), and threshold current (Ithreshold: I > II = IV > III = V). Evidence from electrical stimulation of the OB and application of receptor antagonists suggests that vPOA neurons receive monosynaptic glutamatergic inputs via the medial olfactory tract, with connectivity varying among neuronal groups [I (24%), II (40%), III (0%), IV (34%) and V (2%)].